Including MRI of a primary bone leiomyosarcoma that radiologically mimics a giant cell tumor - Vorachai Sirikulchayanonta (2018)
The authors present a case of a 42-year-old female who developed a leiomyosarcoma of the right proximal tibia that appeared radiologically similar to a giant cell tumor. Histology revealed spindle cells running in whorl-like fashion with focal atypia and low mitotic figures. The immuno-stains revealed positive reactivity for alpha-smooth muscle (SMA), muscle actin and cytokeratin (AE1/AE3). The authors rendered a diagnosis of low-grade leiomyosarcoma of bone. The lesion was considered a primary lesion since the patient did not have other leiomyomatous tumors. The MRI showed hypo- to iso- signal intensity on T1-weighted imaging and heterogeneous intensity on T2-weighted imaging. This was likely due to admixed fibrotic tissue in the lesion. The tumor cells were not positive for Ebstein-Barr virus by in-situ hybridization as seen in leiomyomatous tumors in immunodeficiency patients.